Pemberdayaan UMKM Warung Kelontong Mbak Lia Dalam Pengelolaan Stok Barang Melalui Penerapan Sistem Pencatatan Sederhana Berbasis Excel - Amrullah Mahardika; Diah Septya Rini; Sumaryanto (LPPI UMN AL WASHLIYAH, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the local economy but still face challenges in inventory management and financial recording. Warung Kelontong Mbak Lia, as one of the MSMEs in Kulon Progo, struggles due to the absence of a structured inventory recording system. This community service program aims to empower the business owner through training and assistance in implementing a simple inventory recording system using Microsoft Excel. The implementation method adopts a participatory approach, including initial surveys, basic training, guided inventory card preparation, evaluation, and follow-up monitoring. The results show that using Excel not only simplifies inventory recording but also improves the owner's understanding of inventory management and financial accountability. This system is proven to be efficient, flexible, and user-friendly without requiring additional costs. With improved inventory records, MSMEs can identify fast-moving products, avoid stockouts, and enhance business decision-making. This program is expected to become a model of empowerment for other MSMEs in adopting more professional and sustainable inventory management practices.